2017
DOI: 10.1038/srep42665
|View full text |Cite
|
Sign up to set email alerts
|

Circulating classical monocytes are associated with CD11c+ macrophages in human visceral adipose tissue

Abstract: Immune cell accumulation in adipose tissue (AT) is associated with the development of AT inflammation, resulting in metabolic dysfunction. Circulating immune cell patterns may reflect immune cell accumulation in expanding AT. However, data linking human leukocytes in blood and AT is lacking. We investigated whether blood immune cell populations are associated with their counterparts in subcutaneous (scAT) or visceral AT (vAT). Flow cytometry was performed on blood, scAT and vAT from 16 lean and 29 obese men. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 33 publications
(40 reference statements)
6
76
2
5
Order By: Relevance
“…In this regard, the β 2 -integrin family member α X β 2 (CD11c/CD18) has been shown to bind fibrinogen through the γ 390-396 domain and is expressed by monocytes/ macrophages (44,45). Inflammatory CD11c + cells are significantly increased in obese adipose tissue and appear to contribute to the obese phenotype (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the β 2 -integrin family member α X β 2 (CD11c/CD18) has been shown to bind fibrinogen through the γ 390-396 domain and is expressed by monocytes/ macrophages (44,45). Inflammatory CD11c + cells are significantly increased in obese adipose tissue and appear to contribute to the obese phenotype (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported an increase of the NK cell number in the adipose tissue of leptin-deficient and diet-induced obese mice as well as in the adipose tissue of obese humans (84,107,132,134,135,137,158). This elevated NK cell number is primarily induced by an increased proliferation of tissue-resident NK cells and to a lesser extent by recruitment from the periphery…”
Section: Tissue-resident Nk Cells In Adipose Tissue Of Obese Individualsmentioning
confidence: 99%
“…Humans and mice have different types of circulating monocytes. The classical subtypes in mouse (Ly‐6G + Ly‐6C high ) and human (CD14 high CD16 − ), which account for ~80% of the circulating monocytes, infiltrate the inflamed tissues and differentiate into inflammatory CD11c + macrophages or DCs . CCL2 (MCP1), which is critical for macrophage‐dependent inflammatory responses in animal models of obesity, binds to the chemokine receptor‐2 (CCR2) and regulates the recruitment of monocyte into the AT .…”
Section: White Adipose Tissue (Wat) In Health and Obesitymentioning
confidence: 99%
“…The classical subtypes in mouse (Ly-6G + Ly-6C high ) and human (CD14 high CD16 − ), which account for~80% of the circulating monocytes, infiltrate the inflamed tissues and differentiate into inflammatory CD11c + macrophages or DCs. [66][67][68] CCL2 (MCP1), which is critical for macrophage-dependent inflammatory responses in animal models of obesity, binds to the chemokine receptor-2 (CCR2) and regulates the recruitment of monocyte into the AT. 69 However, intermediate and non-classical subsets of monocytes (CD16 + CD14 high and CD16 high CD14 dim , respectively) do not express CCR2 but have elevated levels CX3CR1.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%